RETRACTED: Peran modal sosial dalam penanganan bencana pada masyarakat desa rawan bencana Gunung Merapi - Entoh Tohani; Lutfi Wibawa (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2018)
Following a rigorous and careful concerns and consideration in the review of the article published in JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat) entitled “Peran modal sosial dalam penanganan bencana pada masyarakat desa rawan bencana Gunung Merapi” Vol 5, No 2, pp. 128-141, November 2018, DOI: http://dx.doi.org/10.21831/jppm.v5i2.21787This paper has been found to violate the  principles of Jurnal Inovasi Pendidikan IPA Publication and has been retracted.The article has been drawn by the author and will be published in the Jurnal Cakrawala Pendidikan https://journal.uny.ac.id/index.php/cpThe document and its content have been removed from Jurnal Inovasi Pendidikan IPA, and reasonable effort should be made to remove all references to this article.